Scotus’s project of transcendental science - Surzyn, Jacek (Folia Philosophica, 2012)
John Duns Scotus may be treated as a forerunner of a new way of thinking in metaphysics, which according to him is a transcendental science. In fact, he put his entire effort into developing a project of such a metaphysics. It should be taken as an alternative to Thomas Aquinas’ proposal, yet, what needs to be emphasised, the difference between them is not as strong as both Aquinas’ closest students and partisans of Thomism up to today may think. The innovation of Duns was to extend the subjective structure of cognition which enabled in-depth analyses of cognitive abilities of human mind. Thus, Scotus raised a distinctive question concerning the limits of any cognition possible and looked for the answer not in real subjectivity but in formally taken conditions of cognition which, on the one hand, are beyond real sphere, on the other, are not limited simply to the sphere of thinking, that is constituted by human mind. Metaphysics seen along such lines acquires a formal dimension, which, according to Scotus, makes it meet Aristotle’s demands of the most theoretical science concerning being qua being.